2018
DOI: 10.1017/s0954394518000108
|View full text |Cite|
|
Sign up to set email alerts
|

Stylistic variation among mobile speakers: Using old and new regional variables to construct complex place identity

Abstract: This paper examines stylistic variation in the (oh), (o), (aw), and (ay) classes among native speakers of Canadian English living in or just outside either New York City or Washington, DC. Speakers show evidence of change toward US norms for all four vowels, though only (aw) shows consistent style shifting: prevoiceless (aw) is realized with higher nuclei when speakers express ambivalence about or distance from the United States, and lower nuclei when closeness to or positive affect about the United States is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Instead, it looks as if both types of speakers are activating the idea of UK/US English—the stereotypical conception they have of these dialects—and these ideas are shared between migrants and nonmigrants. This claim that stereotypes drive topic-based shifting is consistent with other findings in the topic-based shifting literature: there is inaccurate shifting (Sanchez et al, 2015), and markers and stereotypes shift more than indicators (Bell, 1984; Callary, 1975; Drager et al, 2010; Labov, 1972; Nycz, 2018). 15 Of course, stereotypes are not the opposite of experience, and the nonmigrant speakers in this study at the very least still have a fair amount of media-conveyed exposure to the D2.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Instead, it looks as if both types of speakers are activating the idea of UK/US English—the stereotypical conception they have of these dialects—and these ideas are shared between migrants and nonmigrants. This claim that stereotypes drive topic-based shifting is consistent with other findings in the topic-based shifting literature: there is inaccurate shifting (Sanchez et al, 2015), and markers and stereotypes shift more than indicators (Bell, 1984; Callary, 1975; Drager et al, 2010; Labov, 1972; Nycz, 2018). 15 Of course, stereotypes are not the opposite of experience, and the nonmigrant speakers in this study at the very least still have a fair amount of media-conveyed exposure to the D2.…”
Section: Discussionsupporting
confidence: 87%
“…13.It is worth noting that other recent work looking at topic-based shifting in migrants has found less clear results: Lin (2018) only observed topic-based shifting on one of the variants she investigated, in the wrong direction, and Nycz (2018) found that interviewees shift their pronunciation depending on their affective regional stance in a given moment, but not with broadly defined regional topics. Thus, while the current study confirms that topic can induce shifts in production, we should be wary of assuming that it must (cf., Walker, Szakay, & Cox, 2019), and both methodological factors (reading task; interview; prime-type), and analytical approaches (individual; group) are likely to impact findings.…”
Section: Notesmentioning
confidence: 93%
See 2 more Smart Citations
“…Table 5 did not display properly in the above publication (Nycz, 2018). The table is correctly displayed below.…”
mentioning
confidence: 99%